RESEARCH EXPERIENCE OF FOREIGN THEORIES ABOUT THE ROLE OF THE FIRST LANGUAGE (L1) IN STUDYING THE FOREIGN LANGUAGE (L2) (ON THE EXAMPLE OF AUSTRALIA) - Ekaterina Andreyevna Nishchimova (Вестник Северо-Кавказского федерального университета, 2022)
Is dedicated to the summary of researches of foreign scientists who have contributed a great deal to the promotion of teaching approaches and the valuing of students’ native language while learning the foreign language.